Influence of weather situation on non-CO2 aviation climate effects: the REACT4C climate change functions - Frömming, Christine; Grewe, Volker; Brinkop, Sabine; Jöckel, Patrick; Haslerud, Amund; Rosanka, Simon; van Manen, Jesper; Matthes, Sigrun (Atmospheric Chemistry and Physics, 2021)
The influence of weather situations on non-CO2 aviation climate impact is investigated to identify systematic weather-related sensitivities. If aircraft avoid the most sensitive areas, climate impact might be reduced. Enhanced significance is found for emission in relation to high-pressure systems, jet stream, polar night, and tropopause altitude. The results represent a comprehensive data set for studies aiming at weather-dependent flight trajectory optimization to reduce total climate impact.